A Hybrid Network User Satisfaction-Based Downlink Scheduling in LTE-A Network. (30th May 2022) - Mai, Yi-Ting; Yang, Cheng-Tao
Abstract : To provide high-quality wireless network multimedia services, the 4G/5G network media access control (MAC) layer has adopted the concept of the quality of service (QoS) with different traffic classification service requirements. To efficiently allocate the limited radio resources for achieving a good balance in QoS, throughput and fairness are necessary for the wireless network MAC scheduling issues. While many conventional scheduling schemes only considered one factor: rate or delay, network users might actually have different rate and delay requirements in concert. Herein, a hybrid network user satisfaction-based downlink scheduling approach, namely, max rate delay urgency first (MRDUF), is developed. The MRDUF approach simultaneously considers rate and delay requirements and adopts a hybrid strategy comprising time- and frequency-domain schedulers using two schemes, namely, the first come first serve (FCFS) and max throughput (MT), for the LTE-A downlink environment. Simulation study results have shown that our proposed approach outperforms the conventional scheduling schemes, including MT, proportional fair (PF), blind equal throughput (BET), and earliest deadline first (EDF). The benefit of MRDUF in terms of fairness of satisfaction of rate and delay is demonstrated by the simulation study.